1986
DOI: 10.1002/hep.1840060110
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Significance of Serum Bile Acids in Cirrhosis

Abstract: The value of serum bile acid concentrations for predicting prognosis in cirrhotics was compared with the prognostic significance of clinical and laboratory findings in a prospective 1-year study of 76 patients with cirrhosis. A commercial radioimmunoassay for total serum-conjugated primary bile acids was used. Of 76 patients, 16 died within the follow-up period. The concentration of bile acids in serum more closely correlated with mortality in cirrhosis than the commonly used clinical and laboratory parameters… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0
1

Year Published

1986
1986
2016
2016

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 69 publications
(12 citation statements)
references
References 22 publications
2
9
0
1
Order By: Relevance
“…In rat models, bile acids have been shown to inhibit mitochondrial respiration in a dose dependent manner [79-81] and to enhance the permeability of mitochondria to protons [82]. Our findings, together with those of previous studies [77,83], suggest that plasma bile acids may represent a sensitive non-invasive marker of liver dysfunction in HIV patients.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…In rat models, bile acids have been shown to inhibit mitochondrial respiration in a dose dependent manner [79-81] and to enhance the permeability of mitochondria to protons [82]. Our findings, together with those of previous studies [77,83], suggest that plasma bile acids may represent a sensitive non-invasive marker of liver dysfunction in HIV patients.…”
Section: Discussionsupporting
confidence: 76%
“…Here, we found that intermediate/high FIB-4 and APRI scores and high levels of plasma YKL-40 were associated with increased plasma bile acids in HIV subjects on PI-based ART. Consistent with these findings, elevated serum bile acids have been reported in patients with cirrhosis and chronic HCV infection and were shown to correlate with the severity of liver fibrosis [30,77]. Bile acid levels (GCA and TCA) were positively correlated with acylcarnitines, a marker of incomplete fatty acid β-oxidation and mitochondrial dysfunction [52,78].…”
Section: Discussionmentioning
confidence: 61%
“…19, 21 Elevated serum bile acid concentrations have been shown to be a more sensitive test for the detection of liver cirrhosis than conventional liver function tests. 27, 28 However, the level of TBA in serum does not seem to offer any help in diagnosis or prognosis. 29, 30 The present study is designed to characterize the alteration of serum bile acid profiles associated with the pathophysiology of cirrhosis complementary to the conventional biochemical indices.…”
Section: Discussionmentioning
confidence: 99%
“…Serum markers related to bile acid metabolism, e.g. total bile acids [20, 21]or 7α-hydroxycholesterol serum concentrations, were also related to mortality [22, 23]. The same prognostic value has been shown for albumin and postulated for prealbumin serum concentrations [24, 25, 26].…”
Section: Introductionmentioning
confidence: 98%